2019
DOI: 10.3390/microorganisms7020038
|View full text |Cite|
|
Sign up to set email alerts
|

The Form of N Supply Determines Plant Growth Promotion by P-Solubilizing Microorganisms in Maize

Abstract: Phosphate-(P)-solubilizing microorganisms (PSM) are important drivers of P cycling in natural and agro-ecosystems. Their use as plant inoculants to improve P acquisition of crops has been investigated for decades. However, limited reproducibility of the expected effects, particularly under field conditions, remains a major challenge. This study demonstrates that the form of nitrogen fertilization has a significant impact on the performance of various fungal and bacterial PSM inoculants in maize grown on neutra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
47
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 43 publications
8
47
0
2
Order By: Relevance
“…Similar results were reported for P acquisition, plant growth promotion and yield formation of tomato in a drip-irrigated tomato production system with ammonium placement and inoculation of microbial consortia in the Negev desert in Israel (Bradá č ová et al, 2019). The results of Mpanga et al (2019) suggested that the beneficial effects of stabilized ammonium fertilization on PGPM per-formance might be at least partially attributed to an improved root-induced mobilization of P and other sparingly soluble nutrients by the well documented rhizosphere acidification effect of ammonium fertilizers (Neumann and Rö mheld, 2002). Particularly on low P soils with neutral to alkaline pH or after application of sparingly soluble Rock-P fertilizers, this resulted in a starter fertilization effect, improving the vitality status of the plants.…”
Section: Introductionsupporting
confidence: 76%
See 4 more Smart Citations
“…Similar results were reported for P acquisition, plant growth promotion and yield formation of tomato in a drip-irrigated tomato production system with ammonium placement and inoculation of microbial consortia in the Negev desert in Israel (Bradá č ová et al, 2019). The results of Mpanga et al (2019) suggested that the beneficial effects of stabilized ammonium fertilization on PGPM per-formance might be at least partially attributed to an improved root-induced mobilization of P and other sparingly soluble nutrients by the well documented rhizosphere acidification effect of ammonium fertilizers (Neumann and Rö mheld, 2002). Particularly on low P soils with neutral to alkaline pH or after application of sparingly soluble Rock-P fertilizers, this resulted in a starter fertilization effect, improving the vitality status of the plants.…”
Section: Introductionsupporting
confidence: 76%
“…In the latter context, the preferential perform-ance of PGPMs in combination with N-rich organic fertilizers has been repeatedly reported (Abbasi et al, 2015;Thonar et al, 2017;Mpanga et al, 2018;Bradá č ová et al, 2019). Recently, Mpanga et al (2019) found an improved plant performance associated with a wide range of fungal and bacterial PGPMs in combination with stabilized ammonium fertilizers as compared with nitrate fertilization. Tab.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations